ANDROID PROGRAMMING FOR BEGINNERS - THIRD EDITION build in-depth, full-featured android apps... starting from zero programming experience - HORTON, JOHN (PACKT PUBLISHING LIMITED, 2021)
Learn Java, Android, and app development concepts easily with this updated third edition of Android Programming for Beginners. Whether you want to become a professional Android developer or just want to have fun learning Java and Android, this Android Java programming book is what you need.
Includes bibliographical references and index
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Logiciels d'application; Développement; Informatique mobile; COMPUTERS / Languages / Java; COMPUTERS / Programming / Mobile Devices; COMPUTERS / Internet / Application Development; Application software; Development